Willingness to Pay for Long-Term Care for the Elderly: ความยินดีที่จะจ่ายเพื่อการประกันการดูแลระยะยาวสำหรับผู้สูงอายุ - Lapsomboondee, Ampinee; Sukpaiboonwat, Sivalap; Ratniyom, Aotip (Journal of Applied Economics and Management Strategy, 2021)
บทคัดย่อ งานวิจัยเชิงสำรวจนี้มีวัตถุประสงค์เพื่อประเมินมูลค่าความยินดีที่จะจ่ายสำหรับการบริการดูแลระยะยาวสำหรับผู้สูงอายุโดยใช้แนวคิดแบบจำลองทางเลือกและวิเคราะห์ตามแบบจำลองโลจิตแบบผสมโดยใช้ข้อมูลปฐมภูมิจากการรวบรวมข้อมูลโดยใช้แบบสอบถามจำนวน 400 คนในพื้นที่กรุงเทพมหานคร ผลการศึกษาพบว่าการบริการในสถานบริการทั้งแบบเต็มเวลาและแบบชั่วคราวเป็นบริการที่บุคคลมีความยินดีที่จะจ่ายมากที่สุดเท่ากับ 629.90 บาท/เดือน และ 332.50 บาท/เดือน เนื่องจากเป็นบริการที่รองรับการดูแลที่เกินศักยภาพการดูแลโดยครัวเรือน ดังนั้น การพัฒนาระบบบริการดูแลระยะยาวทั้งในสถานบริการและนอกสถานบริการ เริ่มต้นจากการเร่งพัฒนาสถานบริการทั้งแบบเต็มเวลาและแบบชั่วคราวเป็นปัจจัยสำคัญที่ส่งผลต่อการตัดสินใจร่วมจ่ายเพื่อเป็นแหล่งเงินทุนอันจะส่งผลต่อความยั่งยืนของระบบประกันสุขภาพของประเทศไทย ABSTRACT This survey research aimed to analyze the willingness to pay for long-term care services for the elderly, using the choice modelling method, with the analysis using the mixed logit model. The primary data were collected using a questionnaire with four hundred people in the Bangkok metropolitan area. The analysis of the willingness to pay showed that individuals were willing to pay for both full-time and temporary residential services at the most 629.90 baht/month and 332.50 baht/month respectively, since these services support care that exceeds the potential of the household. Therefore, the development of a long-term care insurance system should begin with the development of full-time and temporary health care for elderly people. These actions would become key factors affecting decision-making for co-payments to be a source of funding, which would affect the long-term care insurance system in Thailand.